Biofilm formation in Acinetobacter baumannii was inhibited by PAβN while it had no association with antibiotic resistance - Chen, Lihua (Microbiologyopen, 2020)
This study was conducted to investigate the relationship between Acinetobacter baumannii biofilm formation and antibiotic resistance. Furthermore, the effects of PAβN, a potential efflux pump inhibitor, on A. baumannii biofilm formation and dispersion were tested, and the gene expression levels of efflux pumps were determined to study the mechanisms. A total of 92 A. baumannii isolates from infected patients were collected and identified by multiplex PCR. The antimicrobial susceptibility of A. baumannii clinical isolates was tested by VITEK 2 COMPACT(®). Genotypes were determined by ERIC‐2 PCR. Biofilm formation and dispersion were detected by crystal violet staining. The presence and mRNA expression of efflux pump genes were analyzed by conventional PCR and real‐time PCR, respectively. More than 50% of the A. baumannii strains formed biofilm and were divided into different groups according to their biofilm‐forming ability. Antibiotic resistance rates among most groups did not significantly differ. There were 7 clonal groups in 92 strains of A. baumannii and no dominant clones among the different biofilm‐forming groups. PAβN inhibited A. baumannii biofilm formation and enhanced its dispersion, whereas adeB, adeJ, and adeG and the mRNA expression of adeB, abeM, and amvA showed no differences in the different biofilm‐forming groups. In conclusion, there was no clear relationship between biofilm formation and antibiotic resistance in A. baumannii. The effects of PAβN on A. baumannii biofilm formation and dispersion were independent of the efflux pumps.